New computing techniques in physics research II : proceedings of the Second International Workshop on Software Engineering, Artificial Intelligence and Expert Systems in High Energy and Nuclear Physics : January 13-18, 1992, L'Agelonde France-Telecom - International Workshop on Software Engineering, Artificial Intelligence and Expert Systems in High Energy and Nuclear Physics (2nd : 1992 : L'Agelonde France-Telecom); Perret-Gallix, D. (London : World Scientific Pub., 1992)
40